Desain Lanskap Jalan Gajah Mada Kota Pekalongan untuk Mendukung Program Pariwisata Batik - Amanulloh, Resdo Hafizh Rizqi; hadi, akhmad arifin (ARSITEKTURA, 2021)
Pekalongan City is known as the city of batik and batik accessed by the "Pantura" Highway. The Gajah Mada Street is the main road of Pekalongan city and has become a segment of "Pantura" Highway that important for tourism activities. Gajah Mada Street's landscape design is needed to improve the street corridor's landscape quality and attractiveness for tourism. On the other hand, Pekalongan has a vital characteristic of Batik culture. This study aims to create the landscape design of Gajah Mada Street to Support the Tourism Program of Batik, accompanied by identifying and analyzing the existing site condition of the Gajah Mada Street in Pekalongan City. The design concept applied in this research is Jlamprang batik and parang batik, two of Pekalongan's distinctive geometric-shaped batik pattern. This study's final results are the concept plan, site plan, detailed engineering design, and perspective drawings.